2020
DOI: 10.1038/s41598-020-64469-4
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet antigen 1-6, 9 and 15 in the Iranian population: An anthropological genetic analysis

Abstract: Human platelet antigens (HPAs) are membranous glycoproteins considered as alloantigens due to their polymorphisms. HPA-incompatibility in multiple pregnancies or blood transfusion can induce the development of alloantibodies leading to thrombocytopenia. The frequency of HPAs varies among populations, so that deep knowledge of HPA frequencies will help us to reduce those incompatibilities. Herein, we studied the allele and genotype frequencies of HPA1-6, HPA9, and HPA15 among the Iranians with intra-and inter-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“… 23 HPA3 was the most heterogenous HPA polymorphism, as reported in many other ethnicities. 4 HPA3 is present on the most prevalent GPIIb on the platelet cell membrane. 1 Therefore, the anti-GPIIb/IIIa antibodies may be related to the high prevalence of GPIIb/IIIa and heterogeneity of the located alloantigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 HPA3 was the most heterogenous HPA polymorphism, as reported in many other ethnicities. 4 HPA3 is present on the most prevalent GPIIb on the platelet cell membrane. 1 Therefore, the anti-GPIIb/IIIa antibodies may be related to the high prevalence of GPIIb/IIIa and heterogeneity of the located alloantigens.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequencies of HPA alleles differ between ethnic groups and geographic areas. 3 , 4 These antigens are important and characterized by their immunogenicity of antiplatelet alloantibodies. HPA-associated alloantibodies have been associated with fetal and neonatal alloimmune thrombocytopenia, posttransfusion purpura, and platelet transfusion refractoriness.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large diversity of HPA genotypes have been reported from varied human ethnic groups from a variety of geographical locations (Azizi et al., 2021; Hayashi et al., 2020; Jovanovic Srzentic et al., 2021; Kazemi et al., 2020; Silva‐Malta et al., 2018; Yan et al., 2006). Many of these studies have suggested significant differences in the frequencies between populations.…”
Section: Introductionmentioning
confidence: 99%